ASSOCIATION OF HYPERTHYROIDISM AND BLOOD GLUCOSE LEVELS IN PATIENTS ATTENDING ELOBIED HOSPITAL IN WESTERN SUDAN - Alzubeir Hassaan, Maysoon; Elsonni Abdalla, Badreldin; Mohammed Eltyeb, Majdolin; Yousif Zaki, Hani; Abdalla Agabeldour, Ahmed (Gezira Journal of Health Sciences, 2009)
Objective: The objective of this study was to examine the effect of hyperthyroidism on blood glucose levels. Materials and methods: Comparative descriptive study was done in twenty four patients with hyperthyroidism referred to Elobied hospital during May –July 2008, their ages ranged from 14 to 65 years; thirty three healthy volunteers with matching age and sex were included. Data collected through, clinical evaluation form, questionnaire, and laboratory investigations. Serum concentrations of total triiodothyronine (TT 3 ), total tetariodothyronine (TT 4 ) and thyroid stimulating hormone (TSH) were measured by enzyme linked immune sorbent assay (ELISA) and blood glucose concentrations (BGC) were measured by colorimetric method. Results: The patients showed a concentration of TT4 more than 11.6µg/dl (higher than normal upper limit). The prevalence of glucose intolerance in hyperthyroid patients was 29.17% (n= 7). The glucose intolerance was significantly correlated with serum TT 4 levels (p=0.006, r=0.252). Conclusion: Glucose intolerance is associated with high TT 4 levels in hyperthyroid patients.